2015
DOI: 10.3393/ac.2015.31.6.222
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Tissue Leptin Expression in Colorectal Cancer Patients

Abstract: PurposeLeptin is encoded by the ob gene and is involved in the control of food intake and energy expenditure. Recent studies have implicated leptin expression to be an indicator of tumor features and prognosis. The purpose of this study was to investigate the association of tissue expression of leptin with the clinicopathological characteristics and clinical outcomes in colorectal cancer patients.MethodsPatients who had undergone a curative surgical resection for a colorectal adenocarcinoma from 2000 to 2004 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 17 publications
4
17
2
Order By: Relevance
“…[ 34 38 ] Although few studies has recommended that the immunohistochemical staining of leptin could be helpful as a marker to predict the characteristics and prognosis of colorectal carcinoma, but conflicting information has been reported. [ 20 25 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 34 38 ] Although few studies has recommended that the immunohistochemical staining of leptin could be helpful as a marker to predict the characteristics and prognosis of colorectal carcinoma, but conflicting information has been reported. [ 20 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 9 ] Several reports have described leptin role in the proliferation, migration, and invasion of tumor cells and how it prevents apoptosis through different ways. [ 10 14 ] Histologically, many studies have attempted to test the relationship between leptin immunoexpression and clinical parameters in several tumors including colorectal cancer, but the findings are controversial, [ 15 25 ] and yet, not much is known about the clinical significance of leptin phenotype in colorectal carcinomas. Thus, the present study investigates the immunohistochemical staining of leptin in colorectal cancer, and assesses the correlation of its expression with the clinical characteristics and follow up information of these neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [26] found that leptin/Ob-R expression was associated with later-stage, easy metastasis and lower grade of disease. Jeong WK [27] also found that leptin expression was inversely associated with nodal stage but was not associated with differentiation, T stage and stage of disease. Guadagni et al [28] looked at both serum leptin and adiponectin levels in patients with primary and metastatic CRC and compared it to controls.…”
Section: Leptinmentioning
confidence: 92%
“…Therefore, the authors concluded that a higher leptin expression level was a predictor of a better oncologic outcome and that high leptin expression in colorectal-cancer tissue might be a good prognostic factor. Assessment of leptin signaling in tumor tissue needs further investigation to determine its possible impact on prognosis [ 12 ].…”
mentioning
confidence: 99%